Relationship between ‘Big Data’, ‘Internet of People &Thing’ and ‘Internet of Signs &Things’ - Sen, Vidhi; Mishra, Priyanka (International Journal of Engineering and Technology, 2018)
This paper will try to determine the co-relationship exist in between â€˜Big Dataâ€™, the â€˜Internet of People and Thingsâ€™ andÂ Â the â€˜Internet of Signs.â€™ Specifically , we will find outÂ various waysÂ through whichÂ the â€˜thingsâ€™ presentÂ in the â€˜Internet of Thingsâ€™ makesÂ â€˜Big Dataâ€™, and the various waysÂ through which both are combined in order to formÂ semiotic â€˜signsâ€™. We will find out how context is important and also the various types ofÂ relationsÂ that exists inÂ between â€˜Big Dataâ€™, the â€˜Internet of People & Thingsâ€™, and the â€˜Internet of Signsâ€™.Â Â